Combined evaluation of conventional MRI, dynamic contrast-enhanced MRI and diffusion weighted imaging for response evaluation of patients with multiple myeloma. Issue 2 (February 2016) - Dutoit, Julie C.; Claus, Eveline; Offner, Fritz; Noens, Lucien; Delanghe, Joris; Verstraete, Koenraad L.
Abstract: Purpose: To evaluate the value of the combined evaluation of SE MRI, dynamic contrast enhanced MRI (DCE-MRI) and diffusion weighted imaging (DWI) in multiple myeloma (MM) patients after treatment compared to the international myeloma working group (IMWG) response criteria. Materials and methods: The retrospective study includes 27 newly diagnosed patients, providing 99 MRI-investigations. Patients were categorized according to the IMWG response criteria. Quantitative assessment was based on signal intensities (SI) of T1-weighted, fat-saturated T2-weighted and b1000 images, apparent diffusion coefficients (ADC) and parameters from time-intensity-curves (TIC) derived from L3. Qualitative visual analysis of conventional MRI-images, b1000-images and TICs, providing a "combined skeletal score", was used to create MRI response criteria. Results: The combined skeletal score could significantly differentiate between subgroups based on IMWG response criteria ( p  = 0.016). The gold standard plasmacytosis could significantly differentiate between subgroups based on MRI response criteria ( p  < 0.001), as well as slope ( p  < 0.001) and ADC ( p  = 0.006). There is a good agreement between IMWG and MRI response criteria (Kendall's coefficient = 0.761). Conclusion: Response evaluation of MM-patients based on the combination of anatomical information from conventional MRI with functional information from DCE-MRI and DWI, is useful for monitoring therapy.